The ANALISIS KESESUAIAN TUMBUH PORANG TERHADAP PARAMETER LINGKUNGAN DI DESA SELELOS KECAMATAN GANGGA KABUPATEN LOMBOK UTARA - Firman Ali Rahman; Raden Didi Kuswara; Nurmiat Nurmiati; Zulkarnain Gazali; Maya Ekaningsih (Jurnal Inovasi Pendidikan dan Sains, 2022)
Porang is one of the root crops belonging to the family Araceae with a specification of the genus Amorphophallus. Porang is currently being developed in various places in Indonesia, one of which is North Lombok Regency with a potential of 1500 ha. The purpose of this study was to determine the suitability of the habitat and environmental parameters of porang growing in Selelos Village, Gangga District, North Lombok Regency. The research method was carried out by random sampling on the porang growing habitat by observing and analyzing the environmental parameters. The results showed that the height of the porang planting site in Selelos village was growing at an altitude between 443-457 m pdl with an average of 452.71 ± 7,476 m pdl, light intensity 200-550 I with an average of 292.86 ± 120.514 I, soil pH 7.8-7.9 or with an average of 7.84±0.053, soil moisture 1.5-6 RH with an average of 2.79±1.752 RH, and soil temperature 27-28°C or with an average 27.71±0.393 °C. The condition of these environmental parameters is still in accordance with the survival of the porang and is well developed in Selelos village, Gangga district, North Lombok regency. Keywords : Habitat, Environmental parameters, Porang.